2020
DOI: 10.1038/s41586-020-2665-2
|View full text |Cite
|
Sign up to set email alerts
|

Structures and distributions of SARS-CoV-2 spike proteins on intact virions

Abstract: April 2020 Nsp3 abcam ab181620 Nucleocapsid Sino Biological 40143-MM05 Validation Commercial antibodies validated as per manufacturers website: Beta actin Sigma A5441 Immunoblot on chicken fibroblast cell extracts Spike Abcam Ab252690 Validated by ELISA on free peptide from SARS-CoV-1 Nsp3 abcam ab181620 Validated by western blot on SARS-CoV-1 infected cells Nucleocapsid Sino Biological 40143-MM05 Validated by western blot with corresponding viruses Eukaryotic cell lines Policy information about cell lines Cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

86
1,243
7
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,072 publications
(1,354 citation statements)
references
References 60 publications
86
1,243
7
18
Order By: Relevance
“…While our results here demonstrate that CR3022 Fab could form a stable complex with SARS-CoV S protein in a prefusion conformation, a recent study reported that prefusion SARS-CoV-2 S protein fell apart upon binding to CR3022 Fab as indicated by cryo-EM [29]. It should be noted that the three-up conformation is much more rarely observed than the other RBD conformations (all-down, one-up, and two-up) in SARS-CoV by cryo-EM [26][27][28], or SARS-CoV-2 by cryo-EM [30][31][32] and cryo-electron tomography [33,34], and could relate to differences in the stability of S trimers in SARS-CoV versus SARS CoV-2 when CR3022 is bound. Further studies will be required to investigate whether such a difference between SARS-CoV-2 and SARS-CoV is related to stability differences in the recombinant spike proteins, or to different dynamics of the RBD on the virus or infected cells.…”
Section: Cr3022-bound Sars-cov S Protein Exhibits a Rare Three-up Conmentioning
confidence: 95%
“…While our results here demonstrate that CR3022 Fab could form a stable complex with SARS-CoV S protein in a prefusion conformation, a recent study reported that prefusion SARS-CoV-2 S protein fell apart upon binding to CR3022 Fab as indicated by cryo-EM [29]. It should be noted that the three-up conformation is much more rarely observed than the other RBD conformations (all-down, one-up, and two-up) in SARS-CoV by cryo-EM [26][27][28], or SARS-CoV-2 by cryo-EM [30][31][32] and cryo-electron tomography [33,34], and could relate to differences in the stability of S trimers in SARS-CoV versus SARS CoV-2 when CR3022 is bound. Further studies will be required to investigate whether such a difference between SARS-CoV-2 and SARS-CoV is related to stability differences in the recombinant spike proteins, or to different dynamics of the RBD on the virus or infected cells.…”
Section: Cr3022-bound Sars-cov S Protein Exhibits a Rare Three-up Conmentioning
confidence: 95%
“…The receptor binding domain (RBD) has been identified as the critical component to initiate virus attachment to ACE2, a cellular receptor for viral infection 33 . Interestingly, the RBD is present in both up and down configurations in the pre-fusion form of S protein, and the up position has been speculated as the prerequisite for interaction with ACE2 6,31 . The furin cleavage at the S1/S2 boundary of SARS-CoV-2 S occurs during viral biosynthesis 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This feature is believed to have emerged during viral transmission from zoonotic host to human 2527 , and is key to SARS-CoV-2 high transmissibility in humans 28,29 . Although robust SARS-CoV-2 infection of human lungs requires a multibasic cleavage site 30 , interestingly, both cleaved and uncleaved versions of S protein co-exist on virions purified from viral culture on Vero cells 31,32 . Thus, it remains unclear how the cleavage provides an advantage for viral transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we designed a second nanoparticle construct in which we deleted the C-terminal 70 residues of the ectodomain and expressed this truncated spike (residues 1-1143) on ferritin (SΔC-Fer). These C-terminal residues are unresolved in the cryo-EM structures of the spike trimer (3,7) and it has been suggested that they have extensive conformational flexibility based on electron microscopy of soluble trimers and viral particles (39)(40)(41). Additionally, this region of the spike contains an immunodominant linear epitope, as determined via analysis of convalescent sera from COVID-19 patients (42,43).…”
Section: Introductionmentioning
confidence: 99%